Identification of key genes as potential diagnostic and therapeutic targets for comorbidity of myasthenia gravis and COVID-19 - Huang, Liyan; Zuo, Yao; Yang, Hui; He, Xiaofang; Zhang, Lin (Frontiers in Neurology, 2024)
Myasthenia gravis (MG) is a chronic autoimmune neuromuscular disorder. Corona Virus Disease 2019 (COVID-19) has a significant impact on the health and quality of life of MG patients and may even trigger the onset of MG in some cases. With the world-wide development of COVID-19 vaccination, several new-onset MG cases or exacerbation following the COVID-19 vaccines have been acknowledged. In light of the potential association between myasthenia gravis (MG) and COVID-19, the underlying molecular mechanism remains to be elucidated. To better understand the common molecule mechanism, we identified 6 differentially expressed genes (DEGs) shared by MG and COVID-19 including SAMD9, PLEK, GZMB, JUNB, NR4A1 and NR1D1. We explored the correlation between the 6 common genes and immune cells in COVID-19 dataset and constructed the nomogram by the machine learning algorithm.The regulatory miRNAs, transcription factors and small molecular drugs targeting the common genes were predicted and the molecular docking was carried out by AutoDock.In the present study, we have identified 6 common DEGs of MG and COVID-19 and explored their immunological effects and regulatory mechanism. The result may provide new insights for further mechanism research.